A case report of idiopathic hypertrophic pachymeningitis - G. Makarevičius; J. Grigaitė; M. Jokubaitis; A. Klimašauskienė (Neurologijos seminarai)
Idiopathic hypertrophic pachymeningitis (IHP) is a condition characterised by diffuse or local thickening and fibrosis of dura matter caused by inflammation of unknown origin. It is a diagnosis of exclusion. Autoimmune disorders (notably ANCA-associated vasculitis (AAV) and IgG4-related disease) pose one of the greatest diagnostic challenges in the differential diagnosis of hypertrophic pachymeningitis (HP). When these conditions are concerned, differential diagnosis without biopsy could not be certain, as there are no specific clinical or radiological features of local (only CNS affecting) AAV, IgG4-related disease, and idiopathic HP. We present a case of a 63-year-old female who attended our department due to severe headache and diplopia. After extensive testing, IHP was diagnosed. However, the patient was reluctant to dural biopsy, leaving the possibility of AAV or IgG4-related disease. Since patients with IHP and secondary HP often exhibit similar clinical and radiological signs, dural biopsy is crucial for the diagnosis. The presented clinical case focuses on the importance of dural biopsy for the exclusion of secondary causes of HP and establishing a definite diagnosis.